2014
DOI: 10.1007/s40140-014-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Volume Management and Resuscitation in Colorectal Surgery

Abstract: The maintenance of intravascular volume during and after colorectal surgery is important in the optimization of perioperative outcomes. Techniques for optimizing cardiac output using minimally invasive monitoring have been studied extensively with many authorities now advocating some form of intraoperative stroke volume optimization. The excess administration of crystalloid solutions causes significant postoperative morbidity yet recent trials investigating the optimal type of fluid to be used have failed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…These conditions can also endanger anastomosis. [22][23][24] Also, increased IAP with pneumoperitoneum leads to reduced blood flow of the liver and kidneys, which prevents lactate from being excreted from the body. [7] Thus, hyperlactatemia can be seen in laparoscopic colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions can also endanger anastomosis. [22][23][24] Also, increased IAP with pneumoperitoneum leads to reduced blood flow of the liver and kidneys, which prevents lactate from being excreted from the body. [7] Thus, hyperlactatemia can be seen in laparoscopic colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Yates et al [22] reported that elevated lactate values at postoperative 3rd hour independently predicted major complications and prolonged length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that all the three fluid protocols were similar in their overall clinical outcomes. In a review article Yates et al [18] described the controversies over perioperative fluid management in colorectal surgery. They reported a randomized study conducted on 202 patients who received goal-directed balanced crystalloid versus goal-directed balanced starch solution.…”
Section: Timementioning
confidence: 99%